TİP 2 DİYABETİK RATLARDA KROM HİSTİDİNATIN YANGI MARKERLARI VE BEYİN ISI ŞOK PROTEİNLERİ ÜZERİNE ETKİLERİ - GENÇOĞLU, HASAN (Fırat Üniveristesi, 2009)
Kromun değişik organik formları batılı ülkelerde diyetsel takviye mikrobesinler olarak sıklıkla kullanılmaktadır. Tip 2 diyabet hastalığında organik kromun; insülin duyarlılığını, insülin reseptör sayısını, hücrelerin glukoz tutabilme kabiliyetini arttırdığı, serum lipitlerinde iyileşmelere neden olduğu bildirilmektedir.Bu çalışmada, insanlarda emiliminin diğer organik krom suplemanlarından daha yüksek olduğu bildirilen krom histidinatın (Cr-His); yağlı diyetle beslenen ve deneysel tip 2 diyabet oluşturulmuş ratların serum insulin ve glukoz düzeyleri ile beyin dokusu tümör nekroz faktör-alfa (TNF-?), inter lökin 6 (IL?6), malondialdehit (MDA), glutatyon (GSH), ısı şok proteini 60 (Hsp-60) ve ısı şok proteini 70 (Hsp-70) düzeylerine olan etkileri araştırılmıştır. Bu amaçla, araştırmada 42 adet Wistar ratı (55 günlük) altı guruba ayrıldı. (i) Enerjinin %12' si yağlardan oluşan standart diyetle beslenen grup, Kontrol grubunu (K); (ii) Standart diyet ve CrHis içme suyu ile birlikte günlük 110 mcg/kg verilen grup, K+CrHis grubunu; (iii) Enerjinin %40'ı yağlardan oluşan diyetle (HFD) beslenen grup, HFD grubunu; (iv) HFD diyetle beslenen ve CrHis (Günlük 110 mcg/kg) verilen grup, HFD/CrHis grubunu; (v) HFD ile beslenen ve 2 haftadan sonra streptozotosin (STZ) (STZ, 40 mg/kg i.p.) verilen grup, HFD/STZ grubunu; (vı) HFD ile beslenen ve 2 haftadan sonra streptozotosin (STZ) (STZ, 40 mg/kg i.p.) enjekte edilen ve CrHis (günlük 110 mcg/kg) verilen grup, HFD+STZ+CrHis grubunu oluşturdu. Araştırma 12 haftada sonuçlandırıldı. Kontrol+CrHis ve HFD+CrHis gruplarında kontrol grubuna oranla insülin düzeylerinde artış gözlenirken, HFD+STZ+CrHis grubunda HFD+STZ grubuna oranla daha yüksek insülin seviyeleri tespit edilmiştir (P <0.001). CrHis+STZ verilen ve yağlı diyetle beslenen grupta STZ verilen ve yağlı diyetle beslenen gruba oranla belirgin biçimde kan glukoz seviyelerinde düşme olduğu gözlenmiştir (P <0.001). CrHis uygulaması ile beyin MDA (P <0.0001), TNF- ? (P<0.0001) ve IL?6 (P < 0.0001) düzeyleri HFD ve HFD+STZ gruplarında belirgin biçimde azalmıştır. Beyin dokusu GSH seviyeleri krom ugulaması ile HFD ve HFD+STZ gruplarında; CrHis verilmeyen gruplara oranla daha yüksek miktarda tespit edilmiştir (P<0.001). CrHis uygulamasının HFD ve HFD+STZ gruplarında beyin Hsp60 (P < 0.05) ve Hsp70 (P < 0.05) ekspresyonunda gerileme sağladığı gözlenmiştir.Sonuç olarak bu çalışmada; yağlı diyetle beslenen ratlarda ve deneysel diyabet oluşturulmuş yağlı diyetle beslenen ratlarda CrHis uygulanmasının, serum insülin ve kan glukoz düzeylerini olumlu etkilediği, beyin dokusunda yangı parametreleri ve stres yanıtında iyileşmeler sağladığı tespit edilmiştir.Anahtar Kelimeler: Tip 2 Diyabet, Krom Histidinat, Yüksek Yağlı Diyet, Streptozotosin, TNF- ? , IL?6, MDA, Glutatyon, HSP

Various chromium forms are being regularly used among the western countries as dietary supplement micronutrients. It has been reported that, in type 2 diabetes, organic chromium is capable of improving insulin sensitivity, insulin receptor number, plasma lipids and glucose uptake ability of the cells.In this study effects of chromium histidinate (CrHis), which previously reported was more absorptive by human than the other chromium forms, on plasma glucose and insülin levels with brain tissue malondialdehyde (MDA), glutathione (GSH), tumor necrosis factor-alpha (TNF-?), interleukine-6 (IL?6),heat shock protein 60 (Hsp?60) and heat shock protein 70 (Hsp?70) expressions were researched on high fat fed and experimentally diabetes induced rats. The male Wistar rats (n = 42, 55 days old) were divided into six groups. (i) the group which received a standard diet (12% of calories as fat) was assigned as Control group (C) ; (ii) the group which fed standard diet and concominantly received CrHis (110 mcg CrHis/kg body weight per day) was assigned as C/CrHis group; (iii) the group that received a high-fat diet (HFD; 40% of calories as fat) was determined as HFD group; (iv) the group which received a high-fat diet (HFD; 40% of calories as fat) and concominantly received CrHis (110 mcg CrHis/kg body weight per day) was determined as HFD/CrHis group, (v) the group which fed as HFD but were injected with streptozotocin (STZ) on day 14 (STZ, 40 mg/kg i.p.) was assigned as HFD/STZ group; (vi) the group which fed as HFD and after two weeks injected STZ concominantly supplemented with 110 mcg CrHis/kg body weight per day, was assigned as HFD/STZ/CrHis group. The research finished in 12 weeks. After our analyses; when we checked the effects of our study about insulin levels, C/CrHis and HFD/CrHis groups had higher amounts of insulin levels than the control group and the insulin levels of HFD/STZ/CrHis group was higher than HFD/STZ group (P <0,001). It was observed that, the blood glucose levels in HFD/STZ/CrHis group were significantly lower in comparison to HFD/STZ group (P <0,001). Brain tissue MDA (P <0.0001), TNF- ? (P<0.0001) and IL?6 (P < 0.0001) levels were significantly decreased in HFD and HFD/STZ groups when supplemented with CrHis. Higher brain tissue GSH levels were established in HFD/CrHis and HFD/STZ/CrHis groups than HFD and HFD/STZ groups respectively (P<0.001). It was seen that brain Hsp?60 P < 0.05) and Hsp?70 (P < 0.05) expressions were decreased in HFD and HFD+STZ groups with CrHis application.In conclusion, Cr-Histidinate supplementation positively effected serum insulin and blood glucose levels and ameliorated inflammatory parameters and also stress responses in brain tissues of high fat fed and STZ treated rats.Keywords: Type 2 Diabetes, Chromium Histidinate, High Fat Diet, Streptozotocin, TNF- ? , IL?6, MDA, Gluthathione, HSP
Effects of chromium histidinate on inflammatory markers and brain heat shock proteins in a rat model of type 2 diabetes
Keywords: Biyoloji